(3QSGdI aj GdYed HGdcQI PGJ GdcQSis - (3bSWG Hf dhbG GdHYdHcj,J (B300 (3g` s
(3ChdgG (B:s
(3GdHGH GdChd ai eYQaI QShe GdcQI hGSeGFgG GdcQI Bdg eDdaI ef faS GdcQI hGdMdbI GdKGHJI YdjgG hGdcQSi GdMGed dgG s
(3BNQgG (B:s
(3GdHGH GdNGeS hGdSJhf ai eYQaI GdHYOjf Ci chcH aQV dfG ef GdchGcH GdKGHJI GdZjQ eQSheI Ydi GdcQI hGddg CYde s
(3HgG fXGe GdJYbjHIs
(3GdeNWhW YHGQI Yf (B65 (3HGHkG GdMRe jUd Edi hQbI hGMO abW ai fUa GdeNWhWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B131s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B865s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs